Erythropoiesis-stimulating agents in gynecological malignancies: A study-level meta-analysis. (March 2016) - Marchetti, C.; De Felice, F.; Palaia, I.; Musio, D.; Muzii, L.; Tombolini, V.; Benedetti Panici, P.
Highlights: Gynecological cancers are the one at highest risk of anemia. Data on erythropoiesis-stimulating agents (ESAs) benefit and risks are discordant. We found significant reduction in transfusion rates. We found no detrimental effect on overall mortality and failures disease. Abstract: This meta-analysis was planned to define the role of erythropoiesis-stimulating agents (ESAs) in gynecological cancer patients, receiving myelosuppressive treatment. Pubmed, Medline and Scopus were searched to select English-language articles. Only randomized controlled trials (RCTs) were included. Endpoints were incidence of transfusions, thrombotic events (TE), deaths, and failures. Odd ratio (OR) with 95% confidence interval (CI) was calculated using fixed or random effects model. In seven RCTs ESAs studies of 892 patients under treatment, use of ESAs correlates with a significant reduction of transfusions rate (OR = 0.35; 95% CI: 0.19–0.65; p = 0.008). OR for overall mortality was 1.10 (95% CI 0.82–1.49; p = 0.53). ESAs OR for disease failure in 5 studies was 1.71 (95% CI: 0.90–3.24; p = 0.1). This meta-analysis, even if limited by few RCTs, suggests that ESAs reduce transfusions without increasing mortality or disease progression in gynecological cancer patients receiving treatment.